2011
DOI: 10.1007/s11684-011-0115-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful kidney transplantation in highly sensitized patients

Abstract: Highly sensitized patients experience an increased number of rejection episodes and have poorer graft survival rates; hence, sensitization is a significant barrier to both access to and the success of organ transplantation. This study reports our experience in kidney transplantation in highly sensitized patients. Fourteen patients with sensitization or high levels of panelreactive antibodies (PRA) were studied. All patients were desensitized with pre-transplant intravenous immunoglobulin (IVIG)/plasmapheresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In addition, the regimen used for desensitization and described above resulted in excellent patient and graft survival, which were comparable to previously reported results [8][9][10]. Episodes of organ rejection episodes were significantly more frequent in the DS patients in the first year after transplantation, which was an expected finding in light of the DS patients' allosensitization before transplantation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the regimen used for desensitization and described above resulted in excellent patient and graft survival, which were comparable to previously reported results [8][9][10]. Episodes of organ rejection episodes were significantly more frequent in the DS patients in the first year after transplantation, which was an expected finding in light of the DS patients' allosensitization before transplantation.…”
Section: Discussionsupporting
confidence: 88%
“…Episodes of organ rejection episodes were significantly more frequent in the DS patients in the first year after transplantation, which was an expected finding in light of the DS patients' allosensitization before transplantation. Other investigators have reported rates of rejection of 24.1% [9] to 28.6% [10] for LDK transplantation. Although rejection was more common in the DS patients in our study, cumulative graft loss was not.…”
Section: Discussionmentioning
confidence: 99%
“…The desensitization protocol varies at each transplant center, and several desensitization protocols have been used to prevent AMR. These protocols have increased the success rate in sensitized recipients [41,43,44]. The common desensitization protocol includes pretransplant apheresis, induction therapy with anti-CD20 antibody and intravenous immunoglobulin, and maintenance therapy with immunosuppressive drugs [45][46][47][48].…”
Section: Apheresis Therapy For Preconditioning Of Pektmentioning
confidence: 99%
“…rATG is advantageous in preventing acute rejection among transplant recipients at high risk [6], especially in human lymphocyte antigen (HLA)-presensitized patients [7]. Therefore, it is the first choice for induction therapy in HLA-presensitized patients undergoing organ transplantation [8,9].…”
Section: Introductionmentioning
confidence: 99%